Fighting for Equal Spiritual Voice: The Case of the “Women of the Wall” - Daphna-Tekoah, Shir; Sharaby, Rachel (Frontiers in Psychology, 2019)
Our study contributes to the ongoing debate about women’s rights and religious feminism. The context for analysis of women’s experiences is the “Women of the Wall” who have been struggling for the past 30 years for their right to practice their spiritual rituals (praying at the Western Wall) in a hegemonic and masculine arena. We suggest that the “Women of the Wall” and their battle for spiritual equality threaten the hegemonic masculinity. Moreover, this feminist battle expands the feminist revolution and the fights for women’s equality to the religious arena which is dominated by the hegemonic masculinity. The implementation of the Listening Guide, a feminist methodology, assists us in uncovering various voices, representing different aspects of the experiences of the “Women of the Wall” in a conﬂict zone. These narratives reveal juxtapositions of feelings of competence, determination and vulnerability and shed light on the women’s struggle for gender equality in a hegemonic masculine domain.